New blood pressure cut off for preeclampsia definition: 130/80 mmHg. (September 2019) - Sisti, Giovanni; Colombi, Irene
Abstract: The classical diagnosis of preeclampsia is usually based on the fulfillment of 3 criteria: pregnancy > 20 weeks of gestation, proteinuria (2+ on dipstick or > 300 mg/24 h) and arterial hypertension ≥ 140/90 mm Hg. The current blood pressure cut off of 140/90 mm Hg was set by the American College of Obstetrics and Gynecology (ACOG)-issued practice bulletin of 2019, the 2013 Task Force and the guidelines prompted by the International Society for the Study of Hypertension in Pregnancy (ISSHP). The evidence on which the current cut-off is based is scarce and not updated. We propose the application of the 2017 American College of Cardiology/American Heart Association (ACC/AHA) guidelines on pregnant women and defining preeclampsia with the new 130/80 blood pressure cut-off.